2018
DOI: 10.5455/sad.13-1543399784
|View full text |Cite
|
Sign up to set email alerts
|

Women who apply therapeutic abortus' state and trait anxiety levels and related factors

Abstract: Bu araştırmanın amacı, bir kadın hastalıkları ve doğum hastanesine terapötik abortus nedeniyle yatırılan kadınların yaşadıkları durumluk-süreklik anksiyete düzeylerinin belirlenmesidir. Araştırmanın verilerinin toplanmasında kadınların sosyo-demografik ve obstetrik özelliklerini sorgulayan 40 sorudan oluşan kişisel bilgi formu ile Spielberger ve arkadaşları tarafından geliştirilmiş olan Durumluk-Sürekli Anksiyete Envanteri kullanılmıştır. Araştırmada terapötik abortus yapılan kadınların durumluk anksiyete puan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…[37] In a study, the trait anxiety scores of women who had health problems during pregnancy were found to be higher than women who did not have any health problems, which also supports our research findings. [38] In our study, the variable of "wanted pregnancy" was associated with the total score obtained from the PCL-C scale. This result explains the 4 th question of the study.…”
Section: Discussionmentioning
confidence: 64%
“…[37] In a study, the trait anxiety scores of women who had health problems during pregnancy were found to be higher than women who did not have any health problems, which also supports our research findings. [38] In our study, the variable of "wanted pregnancy" was associated with the total score obtained from the PCL-C scale. This result explains the 4 th question of the study.…”
Section: Discussionmentioning
confidence: 64%
“…After having a miscarriage, psychological problems such as depression, anxiety, desperation, and guilt may be observed (Bucak et al, 2018). Studies have shown that in the pre-miscarriage period women show distinct anxiety and depressive symptoms, and these psychological effects decrease after miscarriage.…”
Section: Introductionmentioning
confidence: 99%